A LITERATURE REVIEW OF CLUSTER THEORY: ARE RELATIONS AMONG CLUSTERS IMPORTANT?. (23rd January 2018) - Lu, Ren; Reve, Torger; Huang, Jing; Jian, Ze; Chen, Mei
Abstract: Having reviewed 1259 papers on cluster theory, we find that current cluster studies primarily discussed cluster phenomena from either a microlevel or mesolevel. We argue that studying relations among clusters would increase our understanding of clusters, and such a research topic is worth becoming a new research orientation for cluster theory.